In vitro Biomechanical Study of Pulvertaft Tendon Weaving Technique - Chi-Pan Yuen; Chi-Hung Yen; Hon-Bong Leung; Wing-Lim Tse; Pak-Cheong Ho; Leung-Kim Hung (Journal of Orthopaedics, Trauma and Rehabilitation, 2011)
Background/Purposes: The outcome of tendon repair depends on the strength, which allows early active mobilization to achieve better function without rupture. The aims of this study are to assess quantitatively the biomechanical properties and relationship between the number of tendon weaving and suture method using Pulvertaft technique. Results: We found that the load to failure was increased with increasing number of weaves and sutures. From 1-weave to 4-weave single suture samples, the peak load to failure was 9.5 N, 19.7 N, 37.5 N, and 42.6 N, respectively. Based on previous studies, wrist and finger tendons should withstand 1–8 N on passive mobilization. Conclusion: On active mobilization, finger tendon repair need to provide 34 N for immediate mobilization. Therefore, irrespective of number of sutures, both 3- and 4-weave repairs could allow early mobilization biomechanically.